2019
DOI: 10.1093/ofid/ofz017
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Illness Associated With Emergent Human Adenovirus Genome Type 7d, New Jersey, 2016–2017

Abstract: BackgroundHuman adenoviruses (HAdVs) are known causes of respiratory illness outbreaks in congregate settings, but cases and clusters are less well described from community settings in the United States. During December 2016–February 2017, the New Jersey Department of Health received reports of HAdV infections from 3 sources in 3 adjacent counties. We investigated to characterize the epidemiologic, laboratory, and clinical features of this HAdV outbreak.MethodsA case was defined as a New Jersey resident with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Subtype 2 virus, including some known types of HAdV-7 identified by REA (e.g., HAdV-7a, -7b, -7d2, -7d, and -7l), was also first detected in the 1950s. In contrast to subtype 1, subtype 2 viruses have been greatly expanding worldwide since the 1980s [2,4,14,[25][26][27], and this subtype has gradually became the predominant subtype worldwide, causing substantial increases in mortality and morbidity in recent years. In China, a long-term survey of adenoviral-related pneumonia since 1958 indicated that HAdV-7b was the predominant type before 1980; HAdV-7d then became the predominant type from 1980 to approximately 1990 [19,28].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Subtype 2 virus, including some known types of HAdV-7 identified by REA (e.g., HAdV-7a, -7b, -7d2, -7d, and -7l), was also first detected in the 1950s. In contrast to subtype 1, subtype 2 viruses have been greatly expanding worldwide since the 1980s [2,4,14,[25][26][27], and this subtype has gradually became the predominant subtype worldwide, causing substantial increases in mortality and morbidity in recent years. In China, a long-term survey of adenoviral-related pneumonia since 1958 indicated that HAdV-7b was the predominant type before 1980; HAdV-7d then became the predominant type from 1980 to approximately 1990 [19,28].…”
Section: Plos Onementioning
confidence: 99%
“…Among these genotypes, HAdV-3 and -7 are the most common causative agents worldwide [4][5][6][7]; HAdV-7 is the most pathogenic and can cause more severe respiratory illness and higher fatality rates than other HAdV types [8]. Outbreaks of HAdV-7 have been reported at military training bases, school clusters, and communities around the world [2,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Seven species (A-G) and >100 types have been recognized so far. Among them, HAdV-E4, HAdV-B7, and HAdV-B14 cause severe acute respiratory illness, including severe acute respiratory distress syndrome (2). HAdV-B7d, a genome type of HAdV-B7, was originally designated in 1986 using restriction analysis (3) and classified as genotype B7d on the basis of complete genome analysis in 2013 (4).…”
Section: Dispatchesmentioning
confidence: 99%
“…During 2016-2017, a total of 12 cases were reported, including 3 patients in a residential rehabilitation center, 7 college students, and 2 patients at a tertiary care hospital. Four of those 12 case-patients died; all 4 were in 3 adjacent New Jersey counties and had underlying conditions (2,13,14). In 2018, an HAdV-B7d outbreak at multiple facilities in several US regions resulted in the deaths of 11 infants at rehabilitation center in New Jersey and an 18-year-old freshman at the University of Maryland (15).…”
Section: Dispatchesmentioning
confidence: 99%
“…Some adenoviruses have been associated with acute infection of the eye( 3 ), respiratory( 4, 5 ), and gastrointestinal tract( 1, 6 ). In rare cases infections prove fatal, as observed in a recent neonatal infection of HAdV-D56( 7 ), among adult patients in New Jersey with HAdV-B7d( 8 ), and infamously with HAdV-E4 where large epidemics of adenovirus infection have been seen in military recruits( 9, 10 ). However, most fatal infections are observed in immunocompromised individuals( 11 ), such as those suffering from graft versus host disease (GVHD)( 12 ) or HIV( 13, 14 ).…”
Section: Introductionmentioning
confidence: 99%